(untitled) (Al-Mansour Journal, 2022)
Extracting minutia and other features from fingerprint images is one of the most important steps in automatic fingerprint identification and classification. This paper proposes a method for the generation of long and secure code that may be used for multi-purpose applications, such as ATM, coded door locks and other security measures. The method consists of two phases; the first phase is carried out using fingerprint image enhancement and thinning. The second phase consists of extracting minutia, ridge ending, bifurcation and all other features in order to produce initial pattern. Finally, the multi-purposes secure code is generated by applying the one-way MD5 hash function on that pattern. The achieved results are discussed for security improvement. The proposed technique also shows considerable improvement in the minutia detection process in terms of both efficiency and speed.